(untitled) (Global Journal of Science Frontier Research, 2025)
Matter is any substance that has mass and energy Matter has a minimum energy requirement Matter tends to share energy with other matter to form a system of minimum energy formation Matter moves because of this tendency Relevant issues are discussed Examples and evidence are listed to show how the Principles of Matter work